ISLAMIC BUSINESS ETICS PRINCIPLES AND EMPLOYEEâS WELFARE - Yacob Suparno, Falikhatun & (PROCEEDING INTERNASIONAL SEMINAR, 2015)
This study aimed to obtain empirical evidence on the effects of Islamic Business Etics Principles application on Employeeâs Welfare. This study was conducted in Micro, Small, and Medium Enterprises (MSMEs) in Karanganyar, Central Java, Indonesia. The paradigm used in this study was positivistic with hypothesis testing, while the analysis is conducted with Multiple Linear Regression. The results of this study concluded that Islamic Business Etics affects Employeeâs Welfare. Partially, several indicators such as Siddiq, Amanah, and Istiqomah affect employeeâs welfare in MSMEs in Karanganyar, Central Java, while for the indicators such as Tabligh, Fathanah, and Qanaâah does not affect employeeâs welfare. Therefore, sugesstions for the next reseach are (1) to add MSMEsâ owner as subject of the reseach in order to obtain detailed information about the employeesâ welfare, and (2) qualitative research methods can be used to obtain a more detailed and profound information about employeesâ understanding and experience in the implementation of Islamic Business Etics Principles.Keywords: Employeeâs Welfare, Islamic Business Etics, MSMEs